Task Monitoring Information System: Case Study of Task Minder Implementation in PTIK A Class Students Class 2022 Makassar State University - Fauziah; Miftakhul Jannah; Amanda Putri Lestari (Academic Bright Collaboration, 2024)
In the digital age, students face increasing demands to manage various academic assignments and deadlines effectively. Manual task management often leads to missed deadlines, irregularities, and reduced productivity. Therefore, a structured, easy-to-use task monitoring system is needed to support learning efficiency. This research explores Task Minder, a task monitoring system that helps individuals and organizations manage tasks in a structured manner. With user-friendly features such as account creation, task editing, status tracking, and automatic reminders, Task Minder aims to increase productivity and efficiency. A descriptive method is used to describe and analyze this system, through a whitebox approach in the creation of Software Requirements Specification (SRS) documents. Data was collected through interviews, observations, and documentation, then analyzed qualitatively using thematic analysis methods. The results show an increase in user productivity, but also identify some limitations that need to be considered for effective use. Overall, Task Minder makes a real contribution as a digital solution in academic task management, helping students organize work more efficiently, responsively, and integrated with learning needs.